Does Religion Promote Trust? The Role of Signaling, Reputation, and Punishment - Sosis, Richard (2005)
Scholars of religion, including such luminaries as Durkheim, Rappaport, Turner, and Weber, have widely assumed that religion promotes intragroup trust among adherents. Recent applications of signaling theory to religious behavior among economists, cognitive scientists, and evolutionary anthropologists further endorse this assumption. However, trust has not been rigorously or consistently defined across authors, making generalizations difficult to evaluate. Here I follow Bacharach and Gambetta's (2001) behavioral definition of trust and show that the conditions for intragroup trust are often not met in religious communities, especially isolationist and closed communities to which high levels of trust are typically ascribed. Rather, in such communities, cooperation is maintained through institutional structures that effectively punish cheaters and enhance the value of an honest reputation. These groups gainfully facilitate collective action by offering a circumscribed social arena in which reputations can be built, evaluated, rewarded, and efficiently punished. While face-to-face reciprocal relations obviate the need for trusting behavior within closed religious communities, when social groups are fluid, religious practices and symbolic markers are successful in promoting trust among in-group members and anonymous coreligionists who reside in different communities. In addition, these religious badges of identity may be used by non-group members as signals of trustworthiness.